A Literature Review of the Impact of Monetary Policy on the Real Economy through Stock Markets - Han Shujing (SHS Web of Conferences)
Researchers have found that with the implementation of monetary policy, the stock market undergoes certain changes thereby affecting the movement of the real economy. Through the existing research progress and situation of monetary policy on the transmission mechanism of the stock market is categorized and organized objectively. Firstly, the basic transmission channel of monetary policy is categorized into credit transmission channel and bond transmission channel. Secondly, the transmission mechanism of monetary policy is divided into two steps, the first step of the impact of monetary policy on the stock market is the impact of monetary policy on stock prices through the money supply, interest rates, respectively, from the credit transmission channel and the bond transmission channel two routes; the second step of the stock market on the real economy, respectively, the impact of investment and consumption. Comprehensive comparison found that the existing research on the bond transmission channel on the impact of stock prices there are still large differences and shortcomings. It is recommended that the Government pay attention to and improve the transmission mechanism of monetary policy on the stock market to the real economy, so as to enhance the macro-control ability of monetary policy on the real economy.